2007
DOI: 10.1097/fbp.0b013e3280143226
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate and its ethanol transesterification metabolite ethylphenidate: brain disposition, monoamine transporters and motor activity

Abstract: Ethylphenidate is formed by metabolic transesterification of methylphenidate and ethanol. Study objectives were to (a) establish that ethylphenidate is formed in C57BL/6 (B6) mice; (b) compare the stimulatory effects of ethylphenidate and methylphenidate enantiomers; (c) determine methylphenidate and ethylphenidate plasma and brain distribution and (d) establish in-vitro effects of methylphenidate and ethylphenidate on monoamine transporter systems. Experimental results were that: (a) coadministration of ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 52 publications
9
79
0
Order By: Relevance
“…[21,22] It has also been long recognized that ethylphenidate is formed in vivo following co-administration of methylphenidate with alcohol. [25,26] The reaction of governments in the European Union to the challenge posed by NPS can be broadly differentiated into three legal response types. These may consist of a) the application of existing laws designed for consumer-or health-protection and pharmaceutical legislation;…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] It has also been long recognized that ethylphenidate is formed in vivo following co-administration of methylphenidate with alcohol. [25,26] The reaction of governments in the European Union to the challenge posed by NPS can be broadly differentiated into three legal response types. These may consist of a) the application of existing laws designed for consumer-or health-protection and pharmaceutical legislation;…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to MPD, ethylphenidate blocks the norepinephrine transporter less potently [46]. These findings could indicate that there is an imbalance of the interactions which occur between the noradrenergic and the dopaminergic systems within the brain [46]. Methylphenidate administration alone increases locomotor activity.…”
Section: Response Characteristics Of Ethanol Alone and After Chronic mentioning
confidence: 83%
“…Upon MPD/ethanol co-administration in mice, wholebrain concentrations of ethylphenidate were found to be higher in comparison to when methylphenidate was given alone. In comparison to MPD, ethylphenidate blocks the norepinephrine transporter less potently [46]. These findings could indicate that there is an imbalance of the interactions which occur between the noradrenergic and the dopaminergic systems within the brain [46].…”
Section: Response Characteristics Of Ethanol Alone and After Chronic mentioning
confidence: 86%
See 1 more Smart Citation
“…The long term abuse potential is hard to determine without more detailed studies however the pharmacology of ethylphenidate suggests that there is a significant risk of abuse. Ethylphenidate exists as a racemic mixture with -(l) and + (d) isomers, pharmacological studies have shown that the individual isomers have different pharmacological activity [26,27]. In vitro studies on human monoamine transporters 5-HT (SERT), noradrenaline (NET) and dopamine (DAT) expressed in HEK293 cells evaluated the pharmacology of the racemic mixture (-/+) and the individual isomers have shown that, (+) ethylphenidate exhibited potent effects on DAT uptake inhibition (Ki -27 nM), (-/+) ethylphenidate was slightly less potent (Ki -95 nM) and (-) ethylphenidate was inactive (1730 nM).…”
Section: Resultsmentioning
confidence: 99%